Economic Deprivation as a Predictor of the Direction of Lethal Violence: An Analysis of Italian Provinces. Issue 3 (2nd July 2016) - Stack, Steven; Laubepin, Frederique; Vichi, Monica; Minelli, Giada; Lester, David; Ferracuti, Stefano; Girardi, Paolo; Pompili, Maurizio
Abstract : Research on suicide and homicide rates has neglected an integrated model seeking to explain social variation in the direction of lethal violence. The present investigation explores the association between measures of social deprivation on the relative incidence of suicide over homicide in Italian provinces. Data refer to official government sources on lethal violence rates and measures of social deprivation. The central dependent variable (SHR) is the tendency towards suicide measured as the suicide rate divided by the sum of the suicide and homicide rates. Data were available for 102 Italian provinces in the Census year 2001. The percentage of the population marked by two indicators of deprivation (low education, household population density) were negatively associated with the SHR. The results are largely consistent with a stream of previous research that connects deprivation with a relatively high probability for disadvantaged populations to direct aggression outwardly in the form of homicide rather than inwardly in the form of suicide. The present study specifies which elements of deprivation best predict the direction of violence and is the first study for the Italian context.